Variation and Genotypic Stability of Picea mariana (Mill.) B.S.P. in Newfoundland, Canada - Khalil, M.A.K. (JD Sauerlaender's Verlag, 1986)
This paper presents results of a ten-year black spruce (Picea mariana (MILL.) B. S. P.) provenance study in New foundland, Canada. The data on ten-year height, height growth in the field up to ten year age and in the tenth year and diameter at 0.3 m were studied together with evaluation of genotypic stability and productive quality of the provenances. Provenances were significant sources of variation at four locations, where intra-provenance vari ation was small and vice versa at the other three locations. Height growth in the field showed weak east-west and north-south trends in the mainland and Newfoundland Labrador provenances respectively. Greater height growth of the fast-growing provenances was not dependent only on the growth in the nursery but was retained in the field also. Provenances in the fourth quartile had relatively low genotypic stability, which would make choice of suitable provenances difficult if precise information about the en virornnent of the planting site is not available. However, recommendations have been made for planting sites resembling the test locations and for sites whose environ mental conditions are not known or do not resemble those of the test locations.